2011
DOI: 10.1055/s-0031-1271815
|View full text |Cite
|
Sign up to set email alerts
|

Prädiktoren der Teilnahme an einer Nachsorge nach ambulanter Rehabilitation bei erwerbstätigen Rehabilitanden mit chronischen Rückenschmerzen

Abstract: The results indicate that participation in a follow-up programme is often not compatible with employment. We could not satisfactorily explain why women were more likely to participate in the programme. This result could have been related to women's more flexible time schedules. An improvement of the current situation could be achieved by having follow-up programmes closer to the home, by flexible follow-up offerings, alternative follow-up services (e. g. in certified physiotherapy centres and sport clubs) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 14 publications
3
16
0
11
Order By: Relevance
“…This corroborates prior research, suggesting that incongruity of organization and scheduling of aftercare sessions with working life are key aspects of participation rate [7,11,35]. It seems that mechanisms of uptake are, to some extent, comparable between Web-based and face-to-face treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This corroborates prior research, suggesting that incongruity of organization and scheduling of aftercare sessions with working life are key aspects of participation rate [7,11,35]. It seems that mechanisms of uptake are, to some extent, comparable between Web-based and face-to-face treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, 81.6% of the patients reported a low-to-moderate acceptance, which was comparable to previous findings in different clinical settings, such as inpatient diabetic [38], chronic pain [39], or primary care patients [40], and evidence from surveys in the general population [26,27]. Interestingly, acceptance ratings for Web-based aftercare were lower compared to uptake rates of face-to-face-aftercare [7,9]. This was confirmed by a clear face-to-face treatment preference of inpatients in this study, which corresponded to evidence from previous studies [26,27,72].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Currently few patients take part in existing outpatient-treatments following inpatient rehabilitation because of incompatibility with their duties at work / within their families, or poor access to the outpatient rehabilitation facility [11, 12]. For these reasons internet-based interventions seem to be promising, because most people (80% in 2015) in Germany [13] are online and more than half (51.1%) of the German population uses the internet for health related issues [14].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only a limited number of patients are assumed to have access and to use immediate aftercare following inpatient medical rehabilitation [20]. Sibold and colleagues [21] reported that the most frequently given reasons for non-participation in aftercare programs included incompatibility with duties at work (70.7%), too much time investment (46.5%) and poor access to the outpatient rehabilitation facility (34.1%). Accordingly, travelling time proved to be a significant negative predictor for participation.…”
Section: Introductionmentioning
confidence: 99%